THE INFLUENCE OF FUNDING DECISIONS, INVESTMENT DECISIONS, AND FREE CASH FLOW ON FIRM VALUE - Alda Aurellia; Etty Gurendrawati; Gentiga Muhammad Zairin (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze the effect of funding decisions, investment decisions, and free cash flow on company value. This research uses quantitative methods with secondary data in the form of company annual reports. The population of this research consists of companies included in the LQ45 index during the period 2021-2023 with 18 samples and 54 data observations. Sampling was conducted using purposive sampling method. The analysis used in this research is descriptive statistical analysis and panel data regression analysis with the help of Eviews 13 software. The results of this research show that funding decisions have no effect on company value. Investment decisions have a positive effect on company value. Free cash flow has no effect on company value. Companies are expected to manage financial risks in the face of fluctuating market conditions and maintain long-term financial stability.